Cancer Nursing's Potential to Reduce the Growing Burden of Cancer Across the World - Yates, Patsy; Charalambous, Andreas; Fennimore, Laura; Nevidjon, Brenda; So, Winnie K W; Suh, Eunyoung E; Woodford, Emma; Young, Annie M. (My University, 2020)
Cancer is the first or second leading cause of premature death (i.e., at ages 30-69 years) in 134 of 183 countries, and it ranks third or fourth in an additional 45 countries. An estimated 18.1 million new cancer cases and 9.6 million cancer-related deaths occurred worldwide in 2018. The incidence of cancer globally is expected to exceed 27 million new cancer cases per year by 2040 in part due to the aging of the population and greater susceptibility to aging-related diseases such as cancer. This estimated increase in cancer incidence will occur in all countries, but the predicted increase will be proportionately greatest in low and medium countries. Cancer is also a disease associated with significant morbidity. It is estimated that the total annual economic cost of cancer in 2010 was US$1.16 trillion per year.
Keywords: Burden of cancer; Cancer; Cancer nursing; Global burden of cancer; Health care